A contribuição para os direitos fundamentais do pluralismo jurídico das representações sociais da favela de Matrix na cidade do Rio de Janeiro - Terra, José Maria Barreto Siqueira Parrilha (2012)
The city of Rio de Janeiro develops a secular historical process of ethnic, social and geographic segregation. Such process is manifested in urban areas known as favelas. In these places social and legal practices are developed away from those state aids, occurring, that way, the legal pluralism. This paper seeks, through empiricanalytical research, the understanding of how the legal pluralism was historically developed in a specific favela, here called Matrix. This legal phenomenon was investigated in the seventies by Boaventura de Sousa Santos, in a favela in the city of Rio de Janeiro, which he called Pasárgada. Since then, there have been changes concerning the way it happens the conflicts within the favelas. This study then, seeks by means of the theory developed by Boaventura de Sousa Santos, to identify the structural components of law developed in the Matrix, besides studying the articulations of these structural components. The objects of the research are the collected data in the Matrix favela, whose analysis aims at finding specific values of the culture of the local residents. Thus the interviews given by residents and former narcotics dealers, seek to translate a code of “legal” values of the place across the abyssal lines that divide the city of Rio de Janeiro, between the “codified city” and the Favela. It was cogitated the analysis of a legal values code of conduct suitable for the Matrix favela. Therefore, this study follows the method of "extended case studies", developed by Boaventura de Sousa Santos. This study intends to bring questions, ideas and contributions to the development of a new culture of Human Rights based on the theory developed by Joaquín Herrera Flores, where Law is seen as a fluid and ongoing process of struggle, which allows to recognition and dialogues. Thus, it is intended that human rights are questioned in its traditional perspective, which advocates a static and homogenizing universalism – and state owned. Finally, this study seeks through the multi-national constitutionalism, point out ways that go beyond traditional theory of modern constitutional law, so they can recognize various identities separated by historical abyssal lines.